Manajemen Strategik Pendidikan Inklusif Sekolah Menegah Atas - M. Ary Irawan; M. Rasyid Ridlo; Ahmad Muslim (Journal Of Administration and Educational Management (ALIGNMENT), 2022)
The purpose of this study was to describe the planning, implementation, and strategic evaluation of high school inclusive education in Mataram City, West Nusa Tenggara (NTB) Province. The research method is qualitative, with data collection techniques through observation, interviews, and documentation. Analysis of the internal data through three activities, namely data reduction, data display, and conclusion drawing or verification. The results of the study show, 1) Strategic planning, namely first, an analysis of the readiness of school stakeholders as providers of inclusive education. Second, the establishment of an inclusive education resource center. Third, the readiness of facilities and infrastructure; 2) Strategic implementation, namely First, Determine the input of human resources (educators, education staff, & students). Second, implementing a modified curriculum; (3) the strategic evaluation of inclusive education includes its aspects, namely input, process, and output which is carried out regularly and continuously. In conclusion, in general, the strategic management of high school inclusive education in Mataram City, West Nusa Tenggara (NTB) Province runs sustainably, as can be seen from the strategic planning, implementation, and evaluation carried out. Keywords: Strategic Management, Inclusive Education